A novel deficiency of mitochondrial ATPase of nuclear origin - Houstek, J; Klement, P; Floryk, D; Antonická, H; Hermanská, J; Kalous, M; Hansíková, H; Hout'ková, H; Chowdhury, S K; Rosipal, T; Kmoch, S; Stratilová, L; et al. (Human molecular genetics, 1999)
We report a new type of fatal mitochondrial disorder caused by selective deficiency of mitochondrial ATP synthase (ATPase). A hypotrophic newborn from a consanguineous marriage presented severe lactic acidosis, cardiomegaly and hepatomegaly and died from heart failure after 2 days. The activity of oligomycin-sensitive ATPase was only 31-34% of the control, both in muscle and heart, but the activities of cytochrome c oxidase, citrate synthase and pyruvate dehydrogenase were normal. Electrophoretic and western blot analysis revealed selective reduction of ATPase complex but normal levels of the respiratory chain complexes I, III and IV. The same selective deficiency of ATPase was found in cultured skin fibroblasts which showed similar decreases in ATPase content, ATPase hydrolytic activity and level of substrate-dependent ATP synthesis (20-25, 18 and 29-33% of the control, respectively). Pulse-chase labelling of patient fibroblasts revealed low incorporation of [(35)S]methionine into assembled ATPase complexes, but increased incorporation into immunoprecipitated ATPase subunit beta, which had a very short half-life. In contrast, no difference was found in the size and subunit composition of the assembled and newly produced ATPase complex. Transmitochondrial cybrids prepared from enucleated fibroblasts of the patient and rho degrees cells derived from 143B. TK(-)human osteosarcoma cells fully restored the ATPase activity, ATP synthesis and ATPase content, when compared with control cybrids. Likewise, the pattern of [(35)S]methionine labelling of ATPase was found to be normal in patient cybrids. We conclude that the generalized deficiency of mitochondrial ATPase described is of nuclear origin and is caused by altered biosynthesis of the enzyme.
Keywords: Chromosomes, Human; srdeční mitochondrie; membránové proteiny; acidóza laktátová; buněčné jádro; Consanguinity; Cardiomegaly; Membrane Proteins; pokrevní příbuzenství; Mitochondria, Liver; Heart Failure; Carrier Proteins; Mitochondrial Proton-Translocating ATPases; Hepatomegaly; Electrophoresis, Gel, Two-Dimensional; jaterní mitochondrie; mužské pohlaví; mitochondriální protonové ATPasy; Mitochondrial Myopathies; oxidativní fosforylace; kardiomegalie; Acidosis, Lactic; mitochondriální myopatie; Fetal Growth Retardation; Fatal Outcome; Mitochondria, Heart; Proton-Translocating ATPases; Oxidative Phosphorylation; Infant, Newborn; Cell Nucleus; novorozenec; adenosintrifosfatasy; Humans; 2D gelová elektroforéza; protonové ATPasy; Fibroblasts; srdeční selhání; lidské chromozomy; mnohočetné abnormality; hepatomegalie; Abnormalities, Multiple; Adenosine Triphosphatases; transportní proteiny; fatální výsledek; lidé; Male; fibroblasty; růstová retardace plodu